Pengaruh QuizWhizzer terhadap Motivasi Belajar Siswa pada Pembelajaran IPA di SMPN 1 Palangka Raya - Tyarini, Elly Brata; Araina, Elga; Putri, Rahmadyah Kusuma; Rahmawati, Rahmawati; Hartanti, Rio Eka Desi Purwandari (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the effect of QuizWhizzer on student learning motivation in science lessons for eighth graders at SMPN 1 Palangka Raya. This study is quantitative in nature and uses an experimental research method. The research design used in this study is a one-group pre-test and post-test design with one class as the sample, consisting of 28 students. The media used in this study was QuizWhizzer, which is an educational game-based media. The instrument used in data collection was a questionnaire with a 4-point Likert scale, which was a modification of the 5-point Likert scale. The results showed that the average score of student learning motivation after being given treatment at the post-test was 62, which was very good. Data analysis results showed an increase in student learning motivation, accompanied by significant positive changes (sig. 0.000<0.05). Based on these findings, the researcher concluded that the use of QuizWhizzer media had a positive effect on student learning motivation.